Learning technical genres : a blended learning approach - Dževerdanović, Milena (Array, 2020)
Research studies dedicated to the application of blended learning in modern linguistics are on the rise. With the interdisciplinary nature of science and curricula, researchers are combining traditional methods with contemporary digital sources and text processing tools. Regardless of the many methods and approaches recommended, there is no set methodology widely proven to be successful, due to different student profiles, language competences and the learning environment. This paper presents the results of the blended learning approach taken at the University of Montenegro’s Faculty of Maritime Studies in Kotor. The traditional teaching approach has been combined with genre and discourse knowledge, with the support of digital and internet tools. The goal of the research is to demonstrate that students of the English for Specific Purposes (ESP) course may benefit from genre- and linguistics-based knowledge applied in the technical and digital environment. Moreover, it is argued that a corpus- and genre-based approach to teaching professional genres provides an opportunity to enrich ESP classes. This approach has primarily proved to be beneficial in teaching technical and engineering genres. Language precision is the essence of effective language competence.